OLIY TA’LIM MUASSASALARIDAGI TARBIYAVIY ISHLAR JARAYONLARI VA BOSHQARISH MEXANIZMLARIDAGI MAVJUD MUAMMOLAR TAHLILI - Dadaqo‘ziev, M.R. (SCIENCE and SOCIETY, 2024)
This article presents an analysis of existing problems in educational processes and management mechanisms in higher educational institutions. The article will be useful for strengthening the processes of educational work in higher educational institutions.
Keywords: innovative; higher educational institutions; educational work; pedagogical technologies; education